2013
DOI: 10.1590/s0102-86502013000800002
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl-pyruvate reduces lung injury matrix metalloproteinases and cytokines and improves survival in experimental model of severe acute pancreatitis

Abstract: The ethyl-pyruvate diminishes acute lung injury inflammatory response in acute pancreatitis and ameliorates survival when compared to control group, in the experimental model of necrotizing acute pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Administration of EP significantly reduced the lung injury associated with the pancreatitis. Matone et al tested EP and reported similar results to our study in rat lung [38].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Administration of EP significantly reduced the lung injury associated with the pancreatitis. Matone et al tested EP and reported similar results to our study in rat lung [38].…”
Section: Discussionsupporting
confidence: 88%
“…In the current study serum IL-6 was measured as a marker of inflammation and a significant improvement in serum IL-6 levels was obtained with the use of EP. The EP has an inhibitory effect on some of the pro-inflammatory cytokines through the inhibition of NF-κβ, and these may have mediated the observed beneficial effects of EP on ANP, as reflected by pancreatic tissue damage and the overall mortality rate [27, 28, 38].…”
Section: Discussionmentioning
confidence: 99%
“…This theory is supported by the following evidence in which the alveolar-capillary barrier is severely injured and the pulmonary permeability is significantly increased in an experimental acute necrotizing pancreatitis [6]. The anti-inflammatory agent EP (40 mg/kg intraperitoneally injected every 6 h for 48 h) markedly decreases the lung permeability and alleviates pulmonary edema at least partly by reducing pulmonary inflammation and neutrophils infiltration in a couple of experimental SAP models with acute lung injury [6, 10, 52, 53]. Increased local and systemic levels of IL-6 are associated with inflammatory process, including neutrophil infiltration of the alveolar space, resulting in lung injury [54].…”
Section: The Effect Of Ep On Acute Lung Injuriesmentioning
confidence: 99%
“…Pulmonary arterial pressure (PAP) and systemic pressure were measured as described previously. 15 In brief, two catheters were inserted into the main pulmonary artery and the right common carotid artery under fluoroscopic guidance to measure PAP (including diastolic PAP, systolic PAP, and mean PAP) and mean systemic arterial pressure, respectively. The two catheters were linked to a transducer, and the pressure was simultaneously recorded on a multichannel physiologic recorder (PowerLab 8/30; AD Instruments Pty Ltd, Sydney, Australia).…”
Section: Measurement Of Hemodynamic Parametersmentioning
confidence: 99%
“…Treatment with EP has been shown to improve survival or ameliorate organ dysfunction in a wide variety of preclinical models, including models of severe sepsis, acute lung injury, and acute pancreatitis. [13][14][15] Considering the pathophysiology of PAH and the roles of HMGB1 and ROS in the progression of this disease, it is reasonable to hypothesize that inhibition of HMGB1 and ROS might prevent the development of PAH. Indeed, our previous study showed that intraperitoneal injection of EP could attenuate monocrotaline-induced PAH and reverse pulmonary vascular remodeling in rats by inhibiting the release of TNFα and IL-6 and reducing the expression of ET1.…”
Section: Introductionmentioning
confidence: 99%